Submandibular sialolithiasis in pediatric patient. Case report - Cindy Campos-Villanueva; Jorge Téllez-Rodríguez; Rubí López-Fernández (Instituto Nacional de Pediatría, 2014)
Sialolithiasis is an obstructive pathology of the salivary gland character- ized by the formation of stones in the ductal system or parenchyma. Its incidence is greater in the submandibular gland in 85%, 10% to the parotid gland and 5% to the gland sublingual. Its etiology is attributed to the deposition of inorganic material around an organic nest with salivary mucin, desquamated epithelial cells and bacteria as well as to the anatomical distribution of the gland with respect to its excretor conduct. The sialolit is formed by calcium phosphate compound, small amounts of carbonates in the hydroxyapatite form, magnesium, potas- sium and ammonia. On patients with sialolithiasis symptoms hydration is essential, moist has is to be applied and massaged into the affected gland, while sialogogues intake and salivary production promoting stone passage through the conduit. Sometimes the obstruction of the saliva output may be signs and symptoms of an infectious process. Almost half of the submandibular sialoliths are located in the middle third or distal duct and are susceptible to elimination under conservative treatment or lithectomy. Sialolithiasis is an unusual condition in the pediatric patient. This article includes a review of the literature presenting the etiology, diagnosis aids and conservative or surgical treatments.